Free-riders or victims: women's nonparticipation in irrigation management in Nepal's Chhattis Mauja Irrigation Scheme - Zwarteveen, M.Z.; Neupane, N. (International Irrigation Management Institute, 1996)
Examines multiple factors in women's involvement/non-involvement in irrigation in the Chhattis Mauja irrigation scheme in Nepal. Includes an empirical analysis of the livelihood strategies of farm households, documentation of the level and nature of participation of women and men in the water users' organizations, analysis of women's access to irrigation services, and an examination of the need and desirability of increasing the participation of woman in the scheme organization.